2021
DOI: 10.3389/fonc.2021.682968
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Ruthenium(II) Complex With Lapachol Induces G2/M Phase Arrest Through Aurora-B Kinase Down-Regulation and ROS-Mediated Apoptosis in Human Prostate Adenocarcinoma Cells

Abstract: Lapachol is a well-studied natural product that has been receiving great interest due to its anticancer properties that target oxidative stress. In the present work, two novel lapachol-containing ruthenium(II) complexes [Ru(Lap)(dppm)(bipy)]PF6 (1) and [Ru(Lap)(dppm)(phen)]PF6 (2) [Lap = lapachol, dppm = 1,1′-bis(diphosphino)methane, bipy = 2,2′-bipyridine, phen = 1,10-phenantroline] were synthesized, fully characterized, and investigated for their cellular and molecular responses on cancer cell lines. We foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 91 publications
1
8
0
Order By: Relevance
“…BrC was time‐dependent cytotoxic to DU145 spheroids in the resazurin assay, with an IC 50 almost five times higher than that found in a 2D model. Similar results were reported by De Grandis et al (2021) who treated DU145 cells with cisplatin for 24 h and the drug resistance of DU145 cells was three times higher in MCTS than in 2D culture. These findings confirm how cells grown in 2D and 3D models behave differently.…”
Section: Discussionsupporting
confidence: 90%
“…BrC was time‐dependent cytotoxic to DU145 spheroids in the resazurin assay, with an IC 50 almost five times higher than that found in a 2D model. Similar results were reported by De Grandis et al (2021) who treated DU145 cells with cisplatin for 24 h and the drug resistance of DU145 cells was three times higher in MCTS than in 2D culture. These findings confirm how cells grown in 2D and 3D models behave differently.…”
Section: Discussionsupporting
confidence: 90%
“…In the evaluation of the monolayer permeability of Caco-2 cells, it was found that the single layer was formed satisfactorily and that the mean transepithelial electrical resistance (TEER) value was 579.44 ± 38.75 Ω·cm 2 . Values greater than 300 Ω·cm 2 are known to be the most optimal for cell permeability assays . In addition, 1 mL aliquots were collected at different times from the basolateral compartment of monolayer cells.…”
Section: Resultsmentioning
confidence: 99%
“…Values greater than 300 Ω• cm 2 are known to be the most optimal for cell permeability assays. 31 In addition, 1 mL aliquots were collected at different times from the basolateral compartment of monolayer cells. The study of the peptide concentration of the microparticles, after exposure to the cell monolayer, showed the presence of the peptide through the monolayer of 69.29% and 100% of B and C microparticles, respectively, up to 360 min, calculated using Nanodrop equipment (Figure 4).…”
Section: ■ Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, findings suggested that the natural compound lapachol inhibited PKM2, inducing a blockade of glycolysis, decreasing ATP levels and sensitizing melanoma cells to apoptosis [ 211 ]. In addition, in prostate cancers lapachol promotes apoptosis by inducing increase in ROS production and in the transcription of caspase-3 and -9 [ 212 ]. Apoptosis induction by lapachol was also observed in tumors of different histology [ 213 , 214 ].…”
Section: Cell Death and Metabolism In Cancermentioning
confidence: 99%